Unveiling the role of past vapor pressure deficit through soil moisture in driving tropical vegetation productivity - Akash Verma; Subimal Ghosh (Environmental Research Letters, 2024)
The impact of soil moisture (SM) and vapor pressure deficit (VPD) on gross primary productivity (GPP) variability in ecosystems is a topic of significant interest. Previous studies have predominantly focused on real-time associations between SM, VPD, and carbon uptake, attributing SM as the principal driver of GPP variability due to its direct and indirect effects through VPD. Using an information theory-based process network approach, we discovered that the influence of past VPD, mediated through its effects on SM, emerges as the primary driver of GPP variability across tropical regions. The past VPD conditions influence GPP directly and also affect SM in real-time alongside GPP, which subsequently impacts GPP variability. Examining land-atmosphere feedback using information theory reveals that past VPD conditions influence SM, but not the reverse. These causal structures explain the consistent decline in GPP with increasing VPD trends observed in tropical regions, which are not consistent with SM trends. Our findings emphasize the importance of considering the influence of past VPD mediated by SM when analyzing complex land-vegetation-atmosphere interactions.